The Role of SMEs in Rural Development: Access of SMEs to Finance as a Mediator - Khanal, Rajiv (Kalika Journal of Multidisciplinary Research, 2025)
Small and Medium Enterprises (SMEs) are noted to be key players in rural development, especially with regard to their contribution in increasing access to financial services. Nevertheless, there is limited empirical evidence that can explain the mediating role of financial service access in rural development that is driven by SMEs in a South Asian setting. The article utilized cross-sectional survey data on 427 entrepreneurs in Gandaki Province, Nepal, and analyzed them using the Partial Least Squares Structural Equation Modeling (PLS-SEM). The main constructs to be used were SME activity, access to financial services (AFS), and rural development (RD), the reliability and validity were determined through confirmatory factor analysis. The model showed moderate levels of explanatory power on AFS (R2=0.401) and RD (R2=0.691). The output of the effect sizes showed a high indirect effect of the SMEs on rural development due to financial access (f2=1.159), and the direct impact of the SMEs on rural development was only significant (f2=0.014). The mediation analysis proved that the access to finance significantly mediates the effects of SMEs on rural development (b=0.490, t=15.308, p=0.001). The results emphasize that the development in the rural setting led by the SMEs is predominantly done via the enhancement of access to financial services. A combination of comprehensive policy efforts to promote SME development and the growth of rural financial networks can be used to complement each other and increase economic opportunities and the well-being of communities. This paper highlights the need to implement concerted efforts to ensure inclusive and sustainable rural development.